Comprehensive analysis of immune-related genes reveals diagnostic biomarkers and molecular subtypes in diabetic retinopathy - Lin Mu; Zhe Wang; Yaojiani Cao; Xuejun Wang; Xingtao Zhou (PLoS ONE, 2026)
Diabetic retinopathy (DR) is a common microvascular complication of diabetes and one of the primary causes of vision loss; however, its pathogenic mechanisms remain largely unresolved. In recent years, immune dysregulation has been increasingly recognized to be closely associated with DR progression. In the present study, we integrated two GEO datasets to identify immune-related differentially expressed genes (DEGs) associated with DR. After batch effect correction and differential expression analysis, a total of 123 immune-related DEGs were identified. Functional enrichment analysis demonstrated that these genes are primarily associated with immune activation pathways, such as T-cell receptor signaling, natural killer cell–mediated cytotoxicity, and IL-17 signaling. Using least absolute shrinkage and selection operator (LASSO) regression, five key genes (IL10RA, PLAUR, PLAU, VTN, and VGF) were identified and used to construct a diagnostic model with excellent predictive performance. Protein–protein interaction and immune infiltration analyses revealed that these genes are closely associated with immune cell activity, particularly the increased infiltration of resting CD4 memory T cells and M2 macrophages in the DR retina. To validate these findings, an STZ-induced diabetic mouse model was used, with key genes further validated at the protein level via Western blot. In addition, consensus clustering was used to stratify patients with DR into two molecular subtypes with distinct immune characteristics and pathway enrichment patterns. Overall, our study elucidates the immune-related mechanisms underlying DR and highlights PLAUR, PLAU, and VGF as potential immune-associated biomarkers, providing a theoretical basis for precision diagnosis and development of targeted immunotherapeutic strategies for DR.